2024
DOI: 10.1021/acsomega.4c00618
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Speciation, Leaching Behavior, and Environmental Risk Assessment of Trace Elements in the Bottom Ash from Biomass Power Plant

Mu You,
Mai Xu,
Yunhu Hu
et al.

Abstract: Biomass combustion for power generation stands as a pivotal method in energy utilization, offering a promising approach for renewable energy utilization. However, the substantial volume of slag produced by biomass burning plants poses environmental challenges, impeding sustainable energy practices. This article systematically studies the characteristics of ash generated from typical biomass direct combustion power plant ash and analyzes the chemical composition, trace element content characteristics, leaching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
(93 reference statements)
0
1
0
Order By: Relevance
“…When evaluating the environmental risks of BA its physicochemical properties are crucial for infiltration, salinization, leaching, 116 deposition, oxidation, and (de)carbonization. 16,117 By Tao et al 89 multivariate analytical approach identified a trend of increasing BA and carbon content in the next sequence: woody species > herbaceous dicotyledons > C4 graminoids > C3 graminoids.…”
Section: Bioash (Ba): a Final Level In Transformation Of Bio-based Re...mentioning
confidence: 99%
“…When evaluating the environmental risks of BA its physicochemical properties are crucial for infiltration, salinization, leaching, 116 deposition, oxidation, and (de)carbonization. 16,117 By Tao et al 89 multivariate analytical approach identified a trend of increasing BA and carbon content in the next sequence: woody species > herbaceous dicotyledons > C4 graminoids > C3 graminoids.…”
Section: Bioash (Ba): a Final Level In Transformation Of Bio-based Re...mentioning
confidence: 99%